The Budget Contraction Effect: How Contracting Budgets Lead to Less Varied Choice. (June 2015) - Carlson, Kurt A.; Wolfe, Jared; Blanchard, Simon J.; Huber, Joel C.; Ariely, Dan
How do consumers adjust their spending when their budget changes? A common view is that the allocation of one's current budget should not depend on previous budget allocations. Contrary to this, the authors find that when the budget contracts to a particular level, consumers select less variety (as measured by the number of different items with some of the budget allocated to them) than when their budget expands to that same level. This budget contraction effect stems from a reduction in variety under the contracting budget, not from variety expansion under the expanding budget. Evidence from five experiments indicates that the effect is driven by a desire to avoid feelings of loss associated with spreading allocation cuts (relative to reference quantities from previous allocations) across many items.